EXPLORING REFERENCE ACCURACY ON UNDERGRADUATE THESIS OF ENGLISH LANGUAGE AND LITERATURE PROGRAM - Mulyadi, Ari (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This study specifically reports on the referencing accuracy to examine the breached APA sixth edition formatting references rules produced by English language and literature undergraduate students. This study was frame in Aronsky et.al (2005) employed a qualitative descriptive method to describe the breaches and the most breached rules. The selection of data samples was obtained from undergraduate thesis of nine students in English language and literature program in a private college in Bandung. The results showed that the students breached six formatting general rules: 1) not on a new page (3.23%), 2) incorrect formation of the section name (29.03%), 3) spacing errors (22.58%), 4) not listed alphabetically (19.35%), 5) indentation errors (16.13%), and 6) inÂcorrect recording of the entries (9.68%). While based on the type of source, 20 rules in total were breached, which spread in six types of sources i.e., 1) periodicals, 2) books, reference books, and book chapters, 3) technical and research reports, 4) doctoral dissertation/ masterâ€™s thesis, 5) document from web site, and 6) unclear sources. Furthermore, the most breached APA sixth edition formatting references rules are incorrect formation of the section name (29.03%), incorrect formation of book, reference books, and book chapters (17.44%). The result tracks well with Aronsky et.al (2005) that formatting a paper in APA style can be tricky.